Comparison of the effect of aquatic and Thera-band exercise on pain and quality of life in obese people with knee osteoarthritis. - Krishnan, Kogilavani; Abadi, Fariba Hossein; Zainudin, Fairus Fariza; Barati, Amir Hossein; Elumalai, Gunathevan (Journal of Pain Management, 2021)
Knee osteoarthritis (KOA) among obese people is a common joint pain with loss of physical functioning, disability and reduction in quality of life QoL). This study aimed to compare the effect of aquatic and Thera-band exercise on pain intensity and QoL among obese people with KOA. A total of 45 KOA participants with BMI ≥ 27.5 kg.m-² were randomly recruited and randomly assigned into three groups; aquatic (AQG), Thera-band exercise (TBG) and control (CG); carried out the exercise program, two times weekly, 60 minutes per session, for eight weeks. Quality of life was measured using modified KOOS questionnaire with five sub-domains; pain, symptoms, activities of daily living (ADL), sports/ recreation and knee-related QoL. The results showed no significant difference in age, weight, BMI, and KOA involvement background in all groups. The MANCOVA results displayed a significant interaction of group x time effect on all sub-domains of QoL; pain, symptoms, ADL, sports/recreation and total QoL. In addition, pairwise comparisons between groups among QoL sub-domains revealed that there was significant difference between AQG and TBG in all dimensions of QoL (pain, symptom, ADL and knee-related QoL) exception in sports/recreation domain. For overall aquatic exercise could reduce pain and improve QoL greater that Thera-band exercise after eight weeks of the exercise program. As a conclusion, this progressive aquatic exercise program had a superior effectiveness to reduce all dimensions of QoL, although Thera-band exercise cannot be ignored as an effective, simple and inexpensive method to create a self-exercise program among obese people who suffering from KOA.